Kepemimpinan Kepala Desa Dalam Perencanaan Pembangunan Desa Watutau Kecamatan Lore Peore - Lisda Prisilia Tandiborong; Henry A Ruagadi; Arifin Balingki (Fakultas Ekonomi Universitas Kristen Tentena, 2023)
This research was motivated by the development development in Watutau Village, Lore Peore District, which was considered not running efficiently or had not run properly, marked by inadequate facilities and infrastructure for agriculture and village road infrastructure that was quite concerning, which made researchers interested in discussing the problem with the title